Stengården, an East Jutland Occupation Site from the Early Germanic Iron Age: The Problem of Settlement Continuity in Later Iron Age Denmark - Jensen, Stig (Journal of Danish Archaeology, 1982)
Stengården, an East Jutland Occupation Site from the Early Germanic Iron Age. The Problem of Settlement Continuity in Later Iron Age Denmark.